Haemato-Biochemical Changes In Sheep Suffering From Gastrointestinal Parasitism - Amulya, G.; Sudharani, R.; Shareef, M.Ismail; Gopinath , S.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Present study was carried out to assess the effect of gastrointestinal parasitism on haematological and biochemical parameters in sheep. Faecal samples from 68 sheep were collected, out of which 30 samples were found positive and 20 negative, which were used as control for the study. Results indicated that there was decrease in haemoglobin, packed cell volume, total erythrocyte counts, total serum protein, albumin and albumin-globulin ratio. However,the level of neutrophils, total eosinophil count, total leucocyte count, lymphocytes, and globulin increased significantly in the infected sheep. Nonetheless, monocytes, eosinophils, basophils, cholesterol, creatinine were not significantly different between the control and infected animals.